Elucidation of Altered Pathways in Tumor‐Initiating Cells of Triple‐Negative Breast Cancer: A Useful Cell Model System for Drug Screening. (23rd June 2017) - Christensen, Anne G.; Ehmsen, Sidse; Terp, Mikkel G.; Batra, Richa; Alcaraz, Nicolas; Baumbach, Jan; Noer, Julie B.; Moreira, José; Leth‐Larsen, Rikke; Larsen, Martin R.; Ditzel, Henrik J.
Abstract: A limited number of cancer cells within a tumor are thought to have self‐renewing and tumor‐initiating capabilities that produce the remaining cancer cells in a heterogeneous tumor mass. Elucidation of central pathways preferentially used by tumor‐initiating cells/cancer stem cells (CSCs) may allow their exploitation as potential cancer therapy targets. We used single cell cloning to isolate and characterize four isogenic cell clones from a triple‐negative breast cancer cell line; two exhibited mesenchymal‐like and two epithelial‐like characteristics. Within these pairs, one, but not the other, resulted in tumors in immunodeficient NOD/Shi‐scid/IL‐2 Rγ null mice and efficiently formed mammospheres. Quantitative proteomics and phosphoproteomics were used to map signaling pathways associated with the tumor‐initiating ability. Signaling associated with apoptosis was suppressed in tumor‐initiating versus nontumorigenic counterparts with pro‐apoptotic proteins, such as Bcl2‐associated agonist of cell death (BAD), FAS‐associated death domain protein (FADD), and myeloid differentiation primary response protein (MYD88), downregulated in tumor‐initiating epithelial‐like cells. Functional studies confirmed significantly lower apoptosis in tumor‐initiating versus nontumorigenic cells. Moreover, central pathways, including β‐catenin and nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB)‐related signaling, exhibited increased activation in the tumor‐initiating cells. To evaluate the CSC model as a tool for drug screening, we assessed the effect of separately blocking NF‐κB and Wnt/β‐catenin signaling and found markedly reduced mammosphere formation, particularly for tumor‐initiating cells. Similar reduction was also observed using patient‐derived primary cancer cells. Furthermore, blocking NF‐κB signaling in mice transplanted with tumor‐initiating cells significantly reduced tumor outgrowth. Our study demonstrates that suppressed apoptosis, activation of pathways associated with cell viability, and CSCs are the major differences between tumor‐initiating and nontumorigenic cells independent of their epithelial‐like/mesenchymal‐like phenotype. These altered pathways may provide targets for future drug development to eliminate CSCs, and the cell model may be a useful tool in such drug screenings. Stem Cells 2017;35:1898–1912 Abstract : To elucidate signaling pathways preferentially used by breast cancer stem cells (tumor‐initiating cells), but independent of their epithelial‐like/mesenchymal‐like phenotype, we isolated four isogenic cell lines by single cell cloning of a triple‐negative breast cancer cell line and performed quantitative proteomics and phosphoproteomics. Two of the cell line exhibited mesenchymal‐like and two epithelial‐like characteristics. Within these pairs, one, but not the other, resulted in tumors in immunodeficient NOG mice and efficiently formed mammospheres. Quantitative proteomics and phosphoproteomics revealed that the tumor‐initiating cells of both cell types showed down‐regulation of the apoptotic pathway and subsequent functional studies confirmed that tumor‐initiating cells exhibited a lower rate of apoptosis. Further, the tumor‐initiating cells exhibited pathway modulations related to NF‐κB and β‐catenin signaling. The described cell line model is a potentially suitable tool for future drug screening for CSC‐targeting candidates and will provide novel insight to the mechanisms responsible for the tumorigenic phenotype of tumor‐initiating cells in triple‐negative breast cancer.